THE RELATIONSHIP BETWEEN MATERNAL DEPRESSIVE, ANXIOUS, AND STRESS SYMPTOMS DURING PREGNANCY AND ADULT OFFSPRING BEHAVIORAL AND EMOTIONAL PROBLEMS. Issue 2 (30th April 2014) - Betts, Kim S.; Williams, Gail M.; Najman, Jakob M.; Alati, Rosa
<x xml:space="preserve">Abstract</x> Background Prenatal maternal depressive, anxious, and stress symptoms have been found to be associated with child and adolescent behavior problems. In this paper, we investigate their impact on behavior problems and depressive symptoms in adulthood. Methods Participants included 3, 099 mother–offspring pairs from the Mater University Study of Pregnancy (MUSP), an Australian based, prebirth cohort study. We used latent class growth analysis (LCGA) with parallel processes to identify trajectories of maternal depressive, anxious, and stress symptoms over four time periods between the mothers' first clinic visit and 5 years postpregnancy. We fitted the estimates from the maternal trajectories in multivariate logistic regression models to predict internalizing and externalizing behavior at age 21. We adjusted for a wide range of prenatal and postnatal factors, including maternal life events, relationship quality, contact with the new born, as well as concurrent maternal depressive and anxious symptoms and father's history of mental health problem. Results LCGA found seven groups of mothers; one group of mothers exhibited high levels of depressive, anxious, and stress symptoms during pregnancy but not at later time points. Their offspring experienced increased levels of behavior problems and depressive symptoms. Conclusions This paper provides the first evidence that high levels of maternal subjective depressive, anxious, and stress symptoms experienced in early pregnancy may predict internalizing and externalizing behavior problems and depressive symptoms in young adults.